Juodonių piliakalnio gyvenvietė. Chronologiniai ir struktūriniai pokyčiai - Simniškytė, Andra (Archaeologia Lituana, 2002)
The article discusses one of the most widely investigated settlements in Northeast Lithuania, excavated during 1958, 1959 and 1989 (fig. 1, 2, 4). This site is the Iron Age foot settlement of the Juodoniai hillfort. 250 individual artefacts, comprising more than 30 groups of artefacts, were found in the 4 excavated plots (310 m2). The material has already been published a few times (Nakaitė, 1959; Grigalavičienė, 1992). However, both the publications and the excavation methodology have drawn well-founded criticism (Šatavičius, 1994, p. 26). The main failing of the summary monograph is that it is only an elementary description of the material, while the planigraphy and stratigraphy are ignored.The site’s attraction was due to its longevity; it dates from the 1st millenium B.C. to the 11th C. A.D. (foot settlement dates from the 4th C. A.D. to the 11th C. A.D). The several thousand year old cultural continuity described by E. Grigalavičienė emphasized the Brushed Pottery culture’s vitality and decisive role in forming later cultural derivatives. This is a very simplified model of continuous cultural development which does not evaluate the character of bum an activities nor its intensive instability.The abundance of material, the inexaustable possibilities of its use, and summary monograph’s dubious conclusions combine to impel a reinvestigation of the settlement and its history, Having repeatedly looked over the material of this extraordinary settlement (the article is limited to an analysis of individual artefactual data), an attempt was made to understand the prehistoric development of Northeast Lithuania in the 1st millenium A.D. – the beginning of the 2 millenium A.D.: to establish the settlement’s chronological stages, to evaluate the continuity of activities and possibilities of changes in the settlement, to explain the dynamic; of the land’s settlement reflected in the burial site material.Many inaccuracies were noted in the dating of the artefacts upon looking over the material. E. Grigalavičienė searched for artefact analogues in the Lithuanian material, despite Northeast Lithuania’s cultural orientation into areas along the Dauguva River that had arisen geographically and historically. The similarities in material culture imply a synchronization with the local rhythm of life, which led to a readjustment of the dating of the material and led to it being seen as being younger. In the opinion of Latvian researchers, artefacts that were here dated to the 4th–5th C. – bracelets with thickened and perpendicular lines ornamented terminals, triangular double pendants (fig. 3:6) – only appeared and respectively spread in the middle and 2nd half of the 7th C. and end of the 6th–the 7th C. A.D. Analogues with neighbouring countries and the chronological context of the settlement itself prompted a date of the 3rd quarter of the 1st millenium A.D. for the single bone combs with a small loop and their related blank (fig. 3:3). The MIA (Middle Iron Age) artefact group was also supplemented with crutch-like (2nd half of the 7th–8th C.) and many of the crook-like pins (fig. 3:5). All of the other datable artefacts were LIA (Late Iron Age) finds, many of whose chronology was sufficiently substantiated, thus they are not discussed separately. The chronology of the semicircular bone spindle (fig. 3:7), hafted spearhead, a throwing spear’s point sometimes called 6th–7th C. ploughshare, knife-sickle, raised additional doubts which also were adjusted. The dating of single composite bone combs (fig. 3:1), a comb case (fig. 3:2), bronze belt buckle, tweezers, parts of neck-chest ornaments which were not discussed in earlier publications also was defined more precisely.Having discussed and adjusted the identity and chronology of some artefacts, the distribution of the artefacts was evaluated with the help of computer programs, preceded by a division of all the artefacts into several categories according to (1) the material from which they were made and (2) the artefacts’ function. In both cases, the categories were marked by 3 variant symbols which stood for 3 chronological groups of artefacts: (a) undatable and chronologically unclear long-use artefacts: work tools, artefact fragments, clay beads, bone amulets, etc., whose dating became clear later; (b) MIA artefacts; (c) LIA artefacts.Having evaluated the cultural layer’s content in its entirety and in separate 10 cm thick sublayers (fig. 5–9), an uneven vertical and horizontal spread was noticed; this marked the settlement’s abundant activity zones and characterized the sequence of the cultural layer’s formation. Three stages were distinguished: (A), (B–C), and (C), as well as 3 of their influence zones in the southern, northern, and central parts of the settlement. Since almost all of the artefacts upon whose basis the sequence and changes in human activity were established were found in one continuous horizon without any intermediate layers, the artefacts’ character along with the dynamic; of their density were among the more important criteria for distinguishing the development of activity.Two stages with artefacts of different character were distinguished in the settlement’s southern section: the lower (A) and the upper (B–C). The (A) stage, located at a depth of approximately 80/90–150 cm was characterized by the (a) chronological group of finds, among which was an especially large amount of bone-horn and clay artefacts and their fragments (fig. 10), which comprise 80% of all artefacts in the Nr. 1 and Nr. 2 plots. Aside from the rare comb-pendants which deserve a master-made label and their blanks, almost all of the bone-horn and clay artefacts belonged to the work tool group. The artefact types (there are especially many darning needles and spindles, 5 clay beads) were evidence of intensive household activity, which is customarily assumed 10 have been carried out by women. The northern boundary of this activity was marked by an approximately 0.4–05 m high and 2 m wide natural rise in the terrain in plot Nr. 3 (fig. 7A). It would undoubtedly be unsuitable to equate the (A) stage’s relics with that time period’s settlement boundaries. Only in other localities was that sort of activity apparently not dominant and left a slight trace. The (A) stage was one of the MIA phases which, according to the small amount of its (b) chronological group finds and their stratigraphy can be dated to the end of the 6th–middle of the 7th C.After a short-term reorganization, the (A) stage was changed by the (B–C) stage with its characteristic (a), (b), and (c) group artefacts. Some of the artefacts were analogous to those found in the lower stage, which allows the beginning of the (B–C) stage to be defined as the 2nd half of the 7th C. The amount of metal artefacts, especially metal ornaments and their fragments, increased considerably. The number of metal things (60%) increased at the expense of small bone-horn artefacts (10%) (fig. 6). However, with a change in the artefact material percentages and an increase in the amount of metal things, the finds in the group with a household function remained, as had been the case previously, more numerous (50%, ornaments – 35%) (fig. 8). The jointly found MIA (8) and LIA (17) artefacts considerably expanded the stage’s chronological boundaries, but limited the ability of formalizing the various substages of this stage.Only one (B–C) stage was distinguished in the settlements northern section. Abundant activity also began in the investigated settlement’s northern section in the 2nd half of the 7th C. Although they are not particularly clear, certain differences can nevertheless be detected between the settlement’s contemporary northern and southern sections. Fore mostly, slightly more finds with an applied function (47%) were found in the northern section than work tools (43%) (fig. 8). There are also differences in the percentages of things made from certain materials: from clay (23% in the southern section and 6% in the northern section), from metal (28% and 53%, respectively) (fig. 6). 50% of the entire settlement’s iron awls were concentrated in the northern section. Meanwhile there is an especially large amount of iron knives (75%) and spindles (47%) in the southern section artefacts which were not found at all in the northern section (except for 2 spindles) (fig. 11).Based on the artefacts’ character, relationship, and chronology, the assumption is made that the contents of the (B–C) stage reflect various time-transgressive changes within the MIA and LIA, effectively erasing the boundaries between the periods themselves. The contemporaneity of the settlement’s northern and southern sections notwithstanding, they were separate activity areas, which is confirmed by the different artefact types and their character according to their functions or materials.The (C) stage. The latest traces of activity (9th/10th–13th C.) were found in the excavated settlement’s central section. This is the period exclusively of the LIA with solely (c) group artefacts. Their vast majority consisted of bronze ornaments.The dispersion of the foot settlement over the course of the centuries speaks of the sequence of cultural layer formation: the earliest traces of activity (end of the 6th–middle of the 7th C.) are found in the settlement’s southern section. Soon thereafter (2nd half of the 7th C.) a new stage of life (B–C) began during which household activity continued in the settlement’s southern section and was newly taken up in the settlement’s northern section. They were, at least during the MIA period, separated by an intensively unused space in the economic sphere. That space was settled later, approximately in the 10th C. A.D. Late Iron Age traces are already found in all of the excavated plots.By virtue of the finds’ planigraphy, it was possible to distinguish changes in the structure of the investigated part of the settlement. The structural changes are noticeable not only by the content of the noncontemporaneous stages, but also in the (B–C) stages differential traces of activity in the settlement’s northern and southern sections.This revision of the view of the Juodoniai hillfort and settlement material revealed a nonconsecutive development of life in the site’s environs, contrary to the earlier declared cultural continuity. It became clear that when the settlers abandoned the hillfort in the 1st quarter of the 1st millenium, its base was not settled immediately, but rather only a few centuries later. The changes that occurred in the hillfort’s surroundings coincided with cultural changes: in the 1st quarter of the 1st millenium A.D., Northeast Lithuania’s Stroked Pottery culture was replaced by North Lithuania’s and South Latvia’s Stone-Wreathed Barrow culture, whose elements (harrows with stone wreaths) became the representative features of the land in the 2nd quarter of the 1st millenium A.D. Their abundance in the 3rd–4th C. is inversely proportional to the shortage of settlements. The crisis apparent in the Juodoniai hillfort and settlement material of the 3rd–end of the 4th C. erases one of the few possibilities that at least a portion of the Stone-Wreathed Barrow culture took up residence in foot settlements. Although one of the articles aims was geared toward an explanation of the “crises” apparent in the burial site’s material in the 2nd half of the 5th C. to the end of the 6th C. (Simniškytė A. 2001) by virtue of the long-lived settlement areas’ data, an even longer pause became apparent as a result. Both “catastrophic” periods coincided only with the final phase of the Stone-Wreathed Barrow culture. Based on the Baltic region’s archaeological experience, the reasons for the distinct disproportions between the burial sites and settlements in the 1st millenium’s 2nd quarter should be sought not in some “special life-style”, but in a limited research methodology. A simultaneous effort must be made to fill in its gaps by intensifying new site surveys and with the aid of environmental science methods.A qualitatively new stage of life began in the Juodoniai foot settlement at the end of the 6th C. True, it was still not the culmination of the region’s prosperity. The MIA here is represented by only 4 artefact groups, while the LIA – by 19 groups. Of course, not having evaluated the changing environmental, geopolitical, social, or technological conditions over the course of the centuries which caused the standard of living at that time, it is not possible to straightforwardly interpret this arithmetic. It is only clear that the Juodoniai hillfort, which has usually figured in the literature as a Middle Iron Age site,lived through both of these periods, until in the 2nd half of the 13 C. it ceased to exist.